2018
DOI: 10.1002/2017gl076901
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Electron and Ion Acceleration Characteristics Observed Over Jupiter's Main Aurora

Abstract: Two new Juno‐observed particle features of Jupiter's main aurora demonstrate substantial diversity of processes generating Jupiter's mysterious auroral emissions. It was previously speculated that sometimes‐observed potential‐driven aurora (up to 400 kV) can turn into broadband stochastic acceleration (dominating at Jupiter) by means of instability. Here direct evidence for such a process is revealed with a “mono‐energetic” electron inverted‐V rising in energy to 200 keV, transforming into a region of broadban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(130 citation statements)
references
References 34 publications
(64 reference statements)
7
119
0
Order By: Relevance
“…In phase space density, this means the spectral slopes at lower energies are often α ≈ 1 to 2, or E −1 to E −2 . The auroral distributions studied by Mauk et al (, ) also show similar spectral shapes at the lower energies. The tail of the distribution at the larger energies, defined as above the peak or rollover in the spectrum, can have spectral slopes that vary dramatically.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In phase space density, this means the spectral slopes at lower energies are often α ≈ 1 to 2, or E −1 to E −2 . The auroral distributions studied by Mauk et al (, ) also show similar spectral shapes at the lower energies. The tail of the distribution at the larger energies, defined as above the peak or rollover in the spectrum, can have spectral slopes that vary dramatically.…”
Section: Discussionmentioning
confidence: 85%
“…For this study, it is important to note that JEDI can measure the energy and angular distributions of ~30 keV to 1 MeV electrons. A single sensor is made up of six solid state detector (SSD) telescopes, each with an instantaneous full width at half maximum FOV of ~9 ° × 17 ° (Mauk et al, ; see their supporting information). The accumulation time during the high rate is ~0.5 s, but we find averaging over 1 second is necessary to avoid poor statistics.…”
Section: Energetic Electron Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the arrival of NASA's Juno spacecraft at Jupiter, the wave-particle interaction processes responsible for auroral acceleration at the giant planets were nevertheless assumed to be similar to what is observed in the terrestrial magnetosphere. Contrary to the initial lack of such observations, later spacecraft passes indicated the presence of strong parallel electric fields, coherent particle acceleration, and inverted-V structures Mauk et al, 2018;Paranicas et al, 2018). Juno also observed ion conics on auroral field lines , which may be the result of field-aligned electron beams and the associated broadband whistler waves (Tetrick et al, 2017) similar to the those observed at Earth although at much higher energies.…”
Section: 1029/2019ja027403mentioning
confidence: 79%